NEGOSIASI PERMAINAN DIGITAL DALAM REKONTEKSTUALISASI DAN POSISIONING PEMBELAJARAN SENI BUDAYA - Fitri Dinarti; Djuli Djatiprambudi; I Nyoman Lodra (Haluan Sastra Budaya, 2020)
This study discusses digital games in the contextualization and positioning of arts and culture education in Indonesia. Furthermore, this research focuses on the history of Indonesian art. The method in this research uses qualitative research that discusses the context of games, education, and technology. Data was collected using observations, interviews, and questionnaires which were conducted from January 2019 to March 2020 with the spatial boundaries of senior high schools in Surabaya, East Java, Indonesia. The data that has been obtained then examined from the point of view of Mihaly Csikszentmihalyi's concept of art education and creativity. The results showed that digital games in arts and culture education in high schools encourage students to be more challenged, by having to switch from treating digital games of consumer goods to cultural artifacts that can have meaning, ideas, and knowledge. In addition, digital games in arts and culture education increase creativity in a complex manner in teachers and students. Increased creativity is based on the exploratory abilities of digital games and their complexity as an interdisciplinary field. Furthermore, digital games in arts and culture education in Indonesia can be positioning themselves as agents of the preservation of Indonesian arts and culture.